2008
DOI: 10.5424/sjar/2008064-359
|View full text |Cite
|
Sign up to set email alerts
|

Fruit quality parameters of some southern highbush blueberries (Vaccinium xcorymbosum L.) grown in Andalusia (Spain)

Abstract: Physical and chemical parameters of fresh berries from three southern highbush ("O'Neal", "Sharpblue" and "Misty") blueberry cultivars grown in Huelva (Southwestern Spain) under two production systems were measured and evaluated. ANOVA applied to data yielded significant differences between production systems for mean fruit size and mean fruit fresh weight (P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Sugar concentration and pH are important parameters for evaluating blueberry quality. This fruit had low pH (2.6), titratable acidity (TTA) of 1.6%, and high amount of soluble sugars (11.2 °Brix), according to the expected range of pH 2.7–3.8, TTA values between 0.3% and 1.3%, and >11 °Brix reported for other blueberry cultivars, these values also being influenced by environmental and growing conditions [ 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 83%
“…Sugar concentration and pH are important parameters for evaluating blueberry quality. This fruit had low pH (2.6), titratable acidity (TTA) of 1.6%, and high amount of soluble sugars (11.2 °Brix), according to the expected range of pH 2.7–3.8, TTA values between 0.3% and 1.3%, and >11 °Brix reported for other blueberry cultivars, these values also being influenced by environmental and growing conditions [ 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 83%
“…The value for the fruit (2.92) was intermediate to those of Highbush cultivars (Molina et al, 2008) (2.80 to 3.20) and similar to those of other cultivars in the Rabbiteye group (Saftner et al, 2008) (2.80 and 3.00).…”
Section: Physicochemical Characterizationmentioning
confidence: 68%
“…vázquez-Araújo et al (2010) found values of 10.4, 12.9 and 10.8 °Brix in the juices of blueberry, blackberry and raspberry fruits, respectively. For mature Lowbush blueberries, Kalt & McDonald (1996) found a mean value of 11.15 °Brix, while Molina et al (2008) showed an average of 11.63 °Brix for Highbush blueberries, and Saftner et al (2008) reported an average of 11.75 °Brix for cultivars of the Rabbiteye group.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…All evaluated cultivars were from the same field conditions (Summer 2009-2010) in order to avoid the influence of growing conditions such as soil, pH, and water that could affect the pH of the fruits [ 17 ]. The pH and °Brix obtained from each fresh cultivar are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The initial pH (fresh fruits) founded in “Duke” (pH = 3.74 ± 0.11) was higher than other blueberry cultivars, while the lowest value was obtained for “Elliott” (pH = 2.9 ± 0.06). The reason for these differences would be the citric acid concentration present in each cultivar, which also depends on genetic differences [ 17 ]. The pH values obtained for all the cultivars were in the range of 2.75–3.81, in agreement with previous literature reports for other different blueberry cultivars [ 18 ].…”
Section: Resultsmentioning
confidence: 99%